HIV among Female Sex Workers in Five Cities in Burkina Faso: A Cross-Sectional Baseline Survey to Inform HIV/AIDS Programs - Henri Gautier Ouedraogo; Odette Ky-Zerbo; Adama Baguiya; Ashley Grosso; Sara Goodman; Benoît Cesaire Samadoulougou; Marcel Lougue; Nongoba Sawadogo; Yves Traore; Nicolas Barro; Stefan Baral; Seni Kouanda (AIDS Research and Treatment)
Background. Female sex workers (FSWs) are considered a vulnerable population for HIV infection and a priority for HIV/AIDS response programs. This study aimed to determine HIV prevalence among FSWs in five cities in Burkina Faso. Methods. FSWs aged 18 and older were recruited using respondent driven sampling (RDS) in five cities (Ouagadougou, Bobo-Dioulasso, Koudougou, Ouahigouya, and Tenkodogo) in Burkina Faso from 2013 to 2014. HIV testing was performed using the HIV testing national algorithm. We conducted bivariate and multivariate logistic regression analysis to assess correlates of HIV in all cities combined (not RDS-adjusted). Results. Among Ouagadougou, Koudougou, and Ouahigouya FSWs, RDS-adjusted HIV prevalence was 13.5% (95% Confidence Interval [CI]: 9.6–18.7), 13.3% (95% CI: 7.6–22.4), and 13.0% (95% CI: 7.6–21.3), respectively, compared to 30.1% (95% CI: 25.5–35.1) among Bobo-Dioulasso FSWs. Factors associated with HIV infection were age (adjusted odds ratio [aOR] = 7.84 95% CI: 3.78–16.20), being married or cohabitating (aOR = 2.43, 95% CI: 1.31–4.49), and history of pregnancy (aOR = 5.24, 95% CI: 1.44–18.97). Conclusion. These results highlight the need to strengthen HIV prevention among FSWs, through behavior change strategies, and improve access to sexual and reproductive health services.